The Soul (Heart) and Its Attributes: An Islamic Perspective With Reference To Self in Western Psychology - Munsoor, Mohamed Safiullah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
It is suggested that the drive for excessive materialistic consumption in every sphere of life is causing an elevation in psychological maladies, with a loss of some key social values. This consumption has accentuated the focus on externalities, while moving away from self-development. With the objective of understanding self-development, this study investigates Islamic and Western psychological viewpoints, with comparisons made of the concept of soul and the self. Multi-sourced referencing of the Qur’an, teachings of the Prophet, as well the analytical works of eminent Islamic and Western scholars, form its methodology. The findings indicate that there is an inner science of self-development that is deeply embedded within the Qur’an and the teachings of the Prophet. Western psychology treats the self in the context of this world and according to its own world view, with methods developed for this purpose. The striking finding in Islam is that self-development forms an integral part of the fabric of the faith; it has an in-depth exposition of the nature of the soul and the tools and methods to discipline it, all with a view to preparing for the next life.